Dual Gate‐Controlled Therapeutics for Overcoming Bacterium‐Induced Drug Resistance and Potentiating Cancer Immunotherapy. (11th May 2021) - Zhang, Xiaodong; Chen, Xiaokai; Guo, Yuxin; Gao, Ge; Wang, Dongdong; Wu, Yinglong; Liu, Jiawei; Liang, Gaolin; Zhao, Yanli; Wu, Fu‐Gen
Abstract: The presence of bacteria in the tumor can cause cancer resistance to chemotherapeutics. To fight against bacterium‐induced drug resistance, herein we design self‐traceable nanoreservoirs that are simultaneously loaded with gemcitabine (an anticancer drug) and ciprofloxacin (an antibiotic) and are decorated with hyaluronic acid for active tumor targeting. The nanoreservoirs have a pH‐sensitive gate and an enzyme‐responsive gate that can be opened in the acidic and hyaluronidase‐abundant tumor microenvironment to control drug release rates. Moreover, the nanoreservoirs can specifically target the tumor regions without eliciting evident toxicity to normal tissues, kill the intratumoral bacteria, and inhibit the tumor growth even in the presence of the bacteria. Unexpectedly, the nanoreservoirs can activate T cell‐mediated immune responses through promoting antigen‐presenting dendritic cell maturation and depleting immunosuppressive myeloid‐derived suppressor cells in bacterium‐infected tumors. Abstract : pH/enzyme‐responsive nanoreservoirs are co‐loaded with anticancer drugs and antibiotics for overcoming bacterium‐induced drug resistance. They can effectively inhibit tumor growth and remarkably activate the immune system in the presence of bacteria. This work presents a safe and efficacious method to reverse bacterium‐induced drug resistance and convert the intratumoral bacteria from foes to friends for cancer therapy.